A microcontroller multicore in FPGAs: detailed architecture and case studies of embedded critical applications. (2017) - Penteado, Cesar Giacomini; Moreno, Edward David; Pereira, FÁ¡bio DacÁªncio
This paper presents the concept and preliminary tests in FPGA of architecture for a flexible multicore microcontroller. It is aimed at intermediate complexity embedded applications. A previous exact characterisation of the microcontroller model and its target applications is a costly-time task, and depends mostly on the engineers' and programmers' experiences. The proposed architecture can aid the development of new applications, since it allows the selection of hardware components useful to the project during the development of the application. We have designed a prototype in FPGA and it is working with seven CPUs. We have used two applications (PID controllers and AES security algorithm), and our results allow to validate the idea and utility of multicore microcontrollers.